Adjustments and economic reforms in the Andean countries: between optimism and despair - Romero, Marco (2016)
The author describes the structural reforms pursued by Andean countries during the nineties. This presentation is accompanied by an evaluation of the results, distributive effects, and impact of these reforms on the social structure, as well as an evaluation of the international con-text in which these reforms were conceived. The article concludes with a critical perspective of the Washington consensus and a call to Andean governments to carry out policies geared towards educational reform, income distribution, employment and equal opportunities.